Exome-Wide Search for Genes Associated With Central Nervous System Inflammatory Demyelinating Diseases Following CHIKV Infection: The Tip of the Iceberg - Alves-Leon, Soniza Vieira; Ferreira, Cristina dos Santos; Herlinger, Alice Laschuk; Fontes-Dantas, Fabricia Lima; Rueda-Lopes, Fernanda Cristina; Francisco, Ronaldo da Silva; Gonçalves, João Paulo da Costa; de Araújo, Amanda Dutra; Rêgo, Cláudia Cecília da Silva; Higa, Luiza Mendonça; Gerber, Alexandra Lehmkuhl; Guimarães, Ana Paula de Campos; et al. (Frontiers in Genetics, 2021)
Chikungunya virus (CHIKV) is a re-emergent arbovirus that causes a disease characterized primarily by fever, rash and severe persistent polyarthralgia, although less than 1% of cases develop severe neurological manifestations such as inflammatory demyelinating diseases (IDD) of the central nervous system (CNS) like acute disseminated encephalomyelitis (ADEM) and extensive transverse myelitis. Genetic factors associated with host response and disease severity are still poorly understood. In this study, we performed whole-exome sequencing (WES) to identify HLA alleles, genes and cellular pathways associated with CNS IDD clinical phenotype outcomes following CHIKV infection. The cohort includes 345 patients of which 160 were confirmed for CHIKV. Six cases presented neurological manifestation mimetizing CNS IDD. WES data analysis was performed for 12 patients, including the CNS IDD cases and 6 CHIKV patients without any neurological manifestation. We identified 29 candidate genes harboring rare, pathogenic or probably pathogenic variants in all exomes analyzed. HLA alleles were also determined and patients who developed CNS IDD shared a common signature with diseases such as Multiple sclerosis (MS) and Neuromyelitis Optica Spectrum Disorders (NMOSD). When these genes were included in Gene Ontology analyses, pathways associated with CNS IDD syndromes were retrieved, suggesting that CHIKV-induced CNS outcomes may share a genetic background with other neurological disorders. To our knowledge, this study was the first genome-wide investigation of genetic risk factors for CNS phenotypes in CHIKV infection. Our data suggest that HLA-DRB1 alleles associated with demyelinating diseases may also confer risk of CNS IDD outcomes in patients with CHIKV infection.